2013
DOI: 10.1155/2013/620837
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Attenuates Traumatic Brain Injury in Rats by Reducing Brain TNF-αContents and by Stimulating Newly Formed Neurogenesis

Abstract: It remains unclear whether etanercept penetrates directly into the contused brain and improves the outcomes of TBI by attenuating brain contents of TNF-α and/or stimulating newly formed neurogenesis. Rats that sustained TBI are immediately treated with etanercept. Acute neurological and motor injury is assessed in all rats the day prior to and 7 days after surgery. The numbers of the colocalizations of 5-bromodeoxyuridine and doublecortin specific markers in the contused brain injury that occurred during TBI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…[13] The expression of proinflammatory cytokines at the site of injury, including IL-1β and TNF-α, regulate precise cellular events that occur within the first few hours of TBI and persist in the neural tissue for several days with cytokines also being detectable on microglia, perivascular macrophages, and astrocytes. [14,15] Most important secondary factors leading to further neuronal death are lipid peroxidation, apoptosis, and development of reactive oxygen species. [16][17][18][19][20] In our study, cellular and biochemical changes were observed in order to assess the actual outcome of TBI in relation to short-term histological damage and cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The expression of proinflammatory cytokines at the site of injury, including IL-1β and TNF-α, regulate precise cellular events that occur within the first few hours of TBI and persist in the neural tissue for several days with cytokines also being detectable on microglia, perivascular macrophages, and astrocytes. [14,15] Most important secondary factors leading to further neuronal death are lipid peroxidation, apoptosis, and development of reactive oxygen species. [16][17][18][19][20] In our study, cellular and biochemical changes were observed in order to assess the actual outcome of TBI in relation to short-term histological damage and cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…A moderate percussion injury was produced by rapidly injecting a small volume of saline into the closed cranial cavity. This reproducible and consistent model is associated with a >100-mm 3 cerebral contusion volume and neurological motor deficit within the first 3 days after injury [21]. Sham-operated animals received all the aforementioned surgical procedures, except the injury.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Chio et al have demonstrated that post-TBI i.p. administration of etanercept in the luid percussion model of brain injury in the rat improves motor deicits at 7 days and increases markers of neurogenesis [246], decreases acute TBI-induced rises in glutamate, the lactate/pyruvate ratio, and improves injury-induced motor deicits [247], cognitive deicits in the passive avoidance task [248], and the severity of ischemia at 3 days post-injury [247,248]. A major barrier to the eicacy of etanercept as a TNF-α inhibitor for AIS and TBI is its poor BBB permeability due to its large size.…”
Section: Biological Response Modiiers In Tbi and Aismentioning
confidence: 96%